Natural degradable packaging material and preparation method thereof

Through a multi-step preparation method, the fiber raw materials treated with enzymatic and ultrasonic crushing are used, combined with modified functional fillers, to form hyperbranched polysiloxane composite modified fillers, which solves the problem of insufficient performance of existing natural degradable and antibacterial food packaging materials, and achieves higher mechanical properties, barrier properties and stability in high temperature and high humidity environments.

CN119663683AInactive Publication Date: 2025-03-21SHANDONG RUNJIA PACKAGING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510191944.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The antibacterial properties, food preservation properties and oil absorption properties of existing natural degradable antibacterial food packaging materials need to be further improved. At the same time, the stability in high-temperature and high-humidity environments is poor, resulting in rapid decline in performance.

Method used

A natural degradable packaging material preparation method is adopted, including raw material pretreatment, functional filler modification, low temperature treatment, paper-forming treatment and coating treatment. This method uses enzymatic decomposition and ultrasonic crushing treatment of fiber raw materials such as wheat straw, corn leaves, bamboo leaves, mangosteen husks, etc., combined with the modification of silane coupling agent and nanocellulose to form hyperbranched polysiloxane composite modified filler to improve the fiber structure and filler distribution, and improve the mechanical properties and barrier properties of the packaging materials.

Benefits of technology

It effectively improves the mechanical properties, oxygen resistance, moisture resistance and oil resistance of packaging materials, and maintains long-term stability in high-temperature and high-humidity environments, significantly improving the overall performance of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a natural degradable packaging material and a preparation method thereof, and belongs to the field of packaging materials. The preparation method of the natural degradable packaging material comprises the following steps: raw material pretreatment, functional filler modification, low-temperature treatment, finished paper treatment and coating treatment. According to the natural degradable packaging material and the preparation method thereof, the problem that the bonding performance of the packaging material and functional auxiliary components is poor can be effectively solved, and the mechanical performance, the oxygen barrier performance, the moisture barrier performance and the oil-proof performance of the packaging material are effectively improved; the stability of the packaging material in a high-temperature and high-humidity environment is further improved, and good performance can be kept for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of packaging materials, in particular to a natural degradable packaging material and a preparation method thereof. Background Art

[0002] Food packaging materials can provide protection for food, and play an irreplaceable role in preventing food from being infected by external microorganisms or other harmful substances and reducing food oxidation. With the rapid development of food technology, the research on food packaging materials has achieved certain results, but there are also some problems.

[0003] There are many food packaging materials that are allowed to be used in the prior art, and common food packaging materials mainly include: plastic, metal, glass, etc. Among them, plastic packaging materials are the most widely used food packaging materials, but there are monomer residues and low molecular weight substances dissolved in the polymerization preparation process; at the same time, in order to improve its performance, stabilizers, lubricants, colorants and other additives are usually added in the preparation process of plastic packaging materials. These additives will migrate from plastics to the food they come into contact with under certain conditions, thereby causing food contamination. Metal packaging materials occupy a certain proportion in the food packaging industry due to their advantages such as rich resources and convenient recycling and processing, but they still have problems such as poor chemical stability and the easy precipitation of metal ions in acidic environments that affect the flavor of food. Glass packaging materials have high stability, and the most notable features are brightness and transparency, but the high transparency of glass can also damage the food in it, and the use of colorants and other substances will also have a certain impact on food safety.

[0004] In recent years, Europe and the United States and other countries have formulated the "Safety Regulations on Migration of Food Contact Packaging Materials and Utensils", which have increasingly stringent performance requirements for food packaging materials, and the trade barriers for packaging materials have increased from a few to dozens; for exporting countries, this has directly led to repeated obstructions in foreign countries for exported food packaging materials due to food contact issues. Functionalization, environmental protection, and safety of food packaging materials have become the mainstream development direction, and natural biodegradable and antibacterial food packaging materials have gradually become a research hotspot.

[0005] Natural degradable antibacterial food packaging materials are generally prepared with natural polymer materials, antibacterial ingredients, etc. as the main raw materials to obtain degradable and antibacterial food packaging materials. Natural degradable antibacterial food packaging materials are easy to degrade in the natural environment, can extend the shelf life of food by inhibiting bacteria, and have certain mechanical properties, air permeability and moisture barrier properties, and have broad application prospects. However, the antibacterial performance, food preservation performance, and oil absorption performance of existing natural degradable antibacterial food packaging materials need to be further improved.

[0006] In view of the above defects, in the prior art, porous inorganic materials are usually added to the raw fiber pulp, and then prepared into fiber base paper; the adsorption performance of the porous inorganic materials is used to improve the adsorption of grease by the packaging material, thereby inhibiting the formation of bacteria. At the same time, the antibacterial properties of food packaging materials are improved by coating chitosan solution on the surface of the fiber base paper. However, the addition of porous inorganic materials to the fiber base paper not only has the problem of poor distribution uniformity, but also weakens the fiber structure of the fiber base paper, directly leading to the instability of the mechanical properties, oxygen barrier properties, moisture barrier properties and oil resistance of the food packaging material. At the same time, the packaging material has poor stability in high temperature and high humidity environments, and its performance decays rapidly, and it cannot maintain its due performance for a long time. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a natural degradable packaging material and a preparation method thereof, which can effectively avoid the problem of poor combination performance between the packaging material and functional auxiliary components, effectively improve the mechanical properties, oxygen barrier properties, moisture barrier properties and oil resistance properties of the packaging material; and further improve the stability of the packaging material in a high temperature and high humidity environment, so as to maintain good performance for a long time.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a natural degradable packaging material, comprising the following steps: raw material pretreatment, functional filler modification, low temperature treatment, paper forming treatment, and coating treatment; The method for pretreating the raw materials is as follows: putting wheat straw, corn leaves, bamboo leaves and mangosteen shells into deionized water, enzymolyzing with lipase and pectinase, and then subjecting to ultrasonic crushing treatment to adjust the water content to 78-80wt% to prepare a pretreated slurry; The method for modifying the functional filler is as follows: hydrolyzing silane coupling agent KH-550 and silane coupling agent KH-602 to obtain a hydrolyzate; adding medical stone and activated carbon into the hydrolyzate, keeping the temperature at 70-75° C. for reaction, and separating to obtain a solid; washing and drying the solid to obtain a functional modified filler; The low-temperature treatment method is to mix the pretreated slurry and the functional modified filler uniformly, cool the mixture to -42°C to -40°C, keep the mixture warm and then return the mixture to room temperature to obtain a composite slurry. The paper processing method comprises the following steps: mixing the composite pulp, modified nanocellulose and cationic polyacrylamide uniformly, and then beating the pulp to obtain a pulped material; making a paper of the pulped material, and drying the paper after forming the paper to obtain semi-dry paper; The preparation method of the modified nanocellulose is to treat the nanocellulose with a modification treatment liquid; the modification treatment liquid is an anhydrous ethanol solution of dendritic polyamide-amine G2; The coating treatment method is to use chitosan solution as coating liquid, coat it on the surface of semi-dried paper, dry it, and place it for equilibrium to obtain a natural degradable packaging material.

[0009] Furthermore, in the raw material pretreatment, the lipase activity is controlled to be 22-24 U / mL, the pectinase activity is controlled to be 30-32 U / mL; the enzymatic hydrolysis temperature is 38-40°C, and the enzymatic hydrolysis time is 2.5-3.5h; The ultrasonic crushing treatment frequency is 32-36KHz, the ultrasonic crushing treatment power is 700-800W, and the ultrasonic crushing treatment time is 40-50min.

[0010] Preferably, in the raw material pretreatment, the weight ratio of wheat straw, corn leaves, bamboo leaves, mangosteen shells and deionized water is 10-12:7-8:4-5:4-5:1500-1600.

[0011] Furthermore, in the modification of the functional filler, silane coupling agent KH-550 and silane coupling agent KH-602 are added to anhydrous ethanol, and after being evenly dispersed, deionized water is added, the pH is adjusted to 4.5-5, and stirred at room temperature for 10-12 hours to obtain a hydrolyzate; Preferably, the weight ratio of silane coupling agent KH-550, silane coupling agent KH-602, anhydrous ethanol and deionized water is 4-4.1:2.1-2.2:60-65:2-2.2.

[0012] Preferably, in the modification of the functional filler, the heat preservation reaction time at 70-75°C is 5-6h; The weight ratio of medical stone, activated carbon and hydrolyzate is 1.6-1.7:3.3-3.5:43-45.

[0013] Preferably, in the low temperature treatment, the cooling rate is 5-6°C / min; the heat preservation and standing time is 5-6h; The weight ratio of the pretreated slurry to the functional modified filler is 100:7-7.3.

[0014] Preferably, in the paper forming process, the beating speed is controlled to be 18000-20000 rpm, and the beating degree is 45-48° SR; After papermaking and forming, the moisture content of the dried paper is reduced by 28-30% compared with the initial moisture content; The weight ratio of the composite pulp, the modified nanocellulose and the cationic polyacrylamide is 100:4-4.5:1.2-1.3.

[0015] Furthermore, the method for modifying nanocellulose is as follows: adding nanocellulose into anhydrous ethanol, dispersing it uniformly, heating it to 65-68° C. under the protection of inert gas, and dripping the modified treatment liquid while keeping the temperature; after the modified treatment liquid is dripped, stirring it while keeping the temperature for 2-2.5 hours, separating and obtaining a solid, washing and drying the solid to obtain modified nanocellulose; Preferably, the concentration of the dendritic polyamide-amine G2 in the modified treatment solution is 10.5-12 wt %; The weight ratio of the nanocellulose to the dendritic polyamide-amine G2 in the modified treatment solution is 5-5.5:1.

[0016] Preferably, in the coating process, the coating amount of chitosan in the coating liquid on the semi-dried paper surface is controlled to be 3.2-3.5 g / m 2 ; The drying temperature is 85-90℃ and the drying time is 15-20min; The temperature of static equilibrium is 22-24°C, the relative humidity of static equilibrium is 48-52%RH, and the time of static equilibrium is 22-24h; The concentration of chitosan in the coating solution is 1-1.2wt%.

[0017] A natural degradable packaging material is prepared by the above-mentioned preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the natural degradable packaging material of the present invention comprises the following steps: in the raw material pretreatment step, wheat straw, corn leaves, bamboo leaves and mangosteen shells are selected as fiber raw materials, and after being hydrolyzed by lipase and pectinase, ultrasonic crushing is performed to obtain a pretreated pulp; by using the long fiber characteristics of bamboo leaves and the antibacterial and antioxidant characteristics of mangosteen shells, combined with the composite enzymatic hydrolysis and ultrasonic crushing process, the packaging material can be endowed with antibacterial properties, inhibit the growth of microorganisms, improve the mechanical properties and barrier properties of the packaging material, and provide the structural stability of the fiber base paper; in the functional filler modification step, a silane coupling agent KH- 550. After the silane coupling agent KH-602 is subjected to composite hydrolysis, it is contacted with medical stone and activated carbon, and then in-situ condensed on the surface to generate hyperbranched polysiloxane, thereby obtaining a hyperbranched polysiloxane composite modified filler (functional modified filler); while improving the uniformity of the distribution of medical stone and activated carbon in the pretreated pulp, the hyperbranched polysiloxane of the functional modified filler forms a strong interface bond with the fibers in the pretreated pulp, thereby improving the fiber structure stability of the fiber base paper and improving the mechanical properties of the packaging material (such as tensile strength, bursting resistance, etc.); and the functional modified filler fills the gaps in the fibers to improve the The barrier property and oil-proof property of the packaging material are improved, and the overall stability of the packaging material is improved; in the low-temperature treatment step, the pretreated pulp is mixed with the functional modified filler and then subjected to low-temperature treatment, and ice crystals are formed by the water in the pulp at low temperature, which further improves the interface bonding between the pretreated pulp and the functional modified filler, improves the uniformity of raw material mixing, and optimizes the overall performance of the packaging material; in the paper-forming step, the composite pulp, modified nanocellulose, and cationic polyacrylamide are mixed for pulping, papermaking, and drying, and the nanocellulose modified by the dendritic polyamide-amine G2 has a bonding and filling effect on the fibers. Use, further improve the mechanical properties, barrier properties and oil resistance of packaging materials, optimize the overall stability of packaging materials; in the coating process, chitosan solution is used as the coating liquid to coat the semi-dry paper, so as to further improve the barrier properties, oil resistance and antibacterial properties of packaging materials; the aforementioned technical means cooperate and work synergistically with each other, which can effectively avoid the problem of poor combination performance between packaging materials and functional auxiliary ingredients, effectively improve the mechanical properties, oxygen barrier properties, moisture barrier properties and oil resistance of packaging materials; and further improve the stability of packaging materials in high temperature and high humidity environments, so as to maintain good performance for a long time.

[0019] (2) The natural degradable packaging material of the present invention has an air permeability of 1.50-1.53 ​​nm / pa·s, an oil resistance level of 12, a surface tension between the packaging material and castor oil of 22-23 mN / m, and an oxygen permeability of 9.2-9.4 cm 3 / m 2 ·day, water vapor transmission rate is 64.1-64.5g / m 2·day, tensile strength is 23.4-23.8MPa, tear strength is 301-306mN, and bursting strength is 213-219kPa.

[0020] (3) The natural degradable packaging material of the present invention has an antibacterial rate of 99.8-99.9% against Escherichia coli within 48 hours and 99.5-99.7% against Escherichia coli within 240 hours; the antibacterial rate of 99.8-99.9% against Staphylococcus aureus within 48 hours and 99.5-99.7% against Staphylococcus aureus within 240 hours.

[0021] (4) The natural degradable packaging material of the present invention, after being placed in an environment with a temperature of 55°C and a relative humidity of 90%RH for 7 days, has an air permeability of 1.60nm / pa·s, an oil resistance level of 12, and an oxygen permeability of 9.7cm 3 / m 2 ·day, the tensile strength can still reach 23.3MPa, the 48h antibacterial rate against Escherichia coli can still reach 99.4%, and the 48h antibacterial rate against Staphylococcus aureus can still reach 99.5%. DETAILED DESCRIPTION

[0022] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific embodiments of the present invention are now described. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0023] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, "first", "second", etc. are used to distinguish similar objects, and are not used to describe a specific order or sequence. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0024] The embodiment of the present invention provides a method for preparing a natural degradable packaging material, which comprises the following steps: raw material pretreatment, functional filler modification, low temperature treatment, paper forming treatment, and coating treatment.

[0025] The method for pretreating the raw materials comprises the following steps: washing wheat straw, corn leaves, bamboo leaves and mangosteen shells respectively, removing dirt and other impurities on the surface, and then drying; then putting the washed and dried wheat straw, corn leaves, bamboo leaves and mangosteen shells into deionized water, heating the water to 38-40° C., adding lipase and pectinase while keeping the water warm, controlling the lipase activity in the pretreated mixture to be 22-24 U / mL, and the pectinase activity to be 30-32 U / mL; keeping the water warm for 2.5-3.5 hours and then killing the enzymes, and then performing ultrasonic crushing treatment, controlling the ultrasonic crushing treatment frequency to be 32-36 KHz, the ultrasonic crushing treatment power to be 700-800 W, and the ultrasonic crushing treatment time to be 40-50 minutes, and after the ultrasonic crushing treatment is completed, adjusting the water content to 78-80wt% to obtain a pretreated slurry.

[0026] In the raw material pretreatment, the weight ratio of wheat straw, corn leaves, bamboo leaves, mangosteen shells and deionized water is 10-12:7-8:4-5:4-5:1500-1600.

[0027] The functional filler modification method comprises the following steps: adding silane coupling agent KH-550 and silane coupling agent KH-602 into anhydrous ethanol, stirring for 20-40 minutes, adding deionized water, adjusting the pH to 4.5-5 with hydrochloric acid, stirring at room temperature for 10-12 hours, and obtaining a hydrolyzate; then adding medical stone and activated carbon into the hydrolyzate, uniformly dispersing by ultrasonication, heating to 70-75°C, stirring and reacting for 5-6 hours at a temperature preservation temperature, and centrifuging at 7000-8000 rpm to obtain a solid, washing the solid to neutrality with deionized water, placing the solid in a vacuum environment of 0.06-0.08 MPa, and drying at 80-85°C to obtain a functional modified filler (i.e., a hyperbranched polysiloxane composite modified filler).

[0028] In the functional filler modification, the weight ratio of silane coupling agent KH-550, silane coupling agent KH-602, anhydrous ethanol and deionized water is 4-4.1:2.1-2.2:60-65:2-2.2; The weight ratio of medical stone, activated carbon and hydrolyzate is 1.6-1.7:3.3-3.5:43-45.

[0029] The low-temperature treatment method is as follows: after the pretreated slurry and the functional modified filler are uniformly mixed, the temperature is reduced to -42°C--40°C at a cooling rate of 5-6°C / min, the temperature is kept at a temperature of 5-6 hours, the temperature is naturally restored to room temperature, the temperature is kept at room temperature for 10-12 hours, and the temperature is stirred at room temperature for 1-2 hours to obtain a composite slurry.

[0030] In the low temperature treatment, the weight ratio of the pretreated slurry to the functional modified filler is 100:7-7.3.

[0031] The paper processing method comprises the following steps: evenly mixing the composite pulp, modified nanocellulose and cationic polyacrylamide, performing a pulping process, controlling the pulping speed to be 18000-20000 rpm, and the pulping degree to be 45-48°SR, to obtain a pulped material; performing a papermaking process on the pulped material, and drying the paper after forming, until the moisture content of the paper is reduced by 28-30% compared with the initial moisture content, to obtain semi-dry paper.

[0032] In the paper-forming process, the weight ratio of the composite pulp, the modified nanocellulose and the cationic polyacrylamide is 100:4-4.5:1.2-1.3.

[0033] The preparation method of the modified nanocellulose comprises the following steps: adding the nanocellulose to 10-12 times the weight of anhydrous ethanol, ultrasonically dispersing for 20-40 minutes, stirring and heating to 65-68° C. in a nitrogen atmosphere, and dripping a modified treatment liquid while keeping the temperature constant; controlling the dripping time of the modified treatment liquid to be 2-2.5 hours; after the dripping of the modified treatment liquid is completed, continuing to keep the temperature constant and stir for 2-2.5 hours, centrifuging at 12000-13000 rpm to obtain a solid, washing the solid with anhydrous ethanol, and drying to obtain the modified nanocellulose.

[0034] In the preparation of the modified nanocellulose, the modified treatment liquid is an anhydrous ethanol solution of dendritic polyamide-amine G2 (PAMAM G2); the concentration of the dendritic polyamide-amine G2 in the modified treatment liquid is 10.5-12wt%; The weight ratio of nanocellulose to the dendritic polyamide-amine G2 in the modified treatment solution is 5-5.5:1.

[0035] The coating treatment method comprises the following steps: adding chitosan to an acetic acid aqueous solution with a mass concentration of 3-4%, stirring and dissolving, and preparing a coating solution; using semi-dried paper as a coating substrate, applying the coating solution to the surface of the semi-dried paper by a Mayer rod coating method, and controlling the coating amount of chitosan in the coating solution on the surface of the semi-dried paper to be 3.2-3.5 g / m 2 After coating, the coating is placed in an environment with a temperature of 85-90°C and dried for 15-20 minutes, and then transferred to an environment with a temperature of 22-24°C and a relative humidity of 48-52%RH, and allowed to stand for 22-24 hours to obtain a natural degradable packaging material.

[0036] In the coating process, the concentration of chitosan in the coating solution is 1-1.2 wt %.

[0037] The embodiment of the present invention also provides a natural degradable packaging material prepared by the above method.

[0038] The present invention is further described below in conjunction with some specific embodiments.

[0039] Example 1 This embodiment provides a method for preparing a natural degradable packaging material, which comprises the following steps: 1. Raw material pretreatment The wheat straw, corn leaf, bamboo leaf and mangosteen shell are washed respectively, and the surface mud and other debris are removed and then dried; then the washed and dried wheat straw, corn leaf, bamboo leaf and mangosteen shell are put into deionized water, the temperature is raised to 38°C, lipase and pectinase are added while keeping warm, and the enzyme activity of lipase in the pretreated mixture is controlled to be 22U / mL, and the enzyme activity of pectinase is controlled to be 30U / mL; after keeping warm and enzymolysis for 2.5 hours, the enzyme is killed, and then ultrasonic crushing treatment is carried out, the ultrasonic crushing treatment frequency is controlled to be 32KHz, the ultrasonic crushing treatment power is 700W, and the ultrasonic crushing treatment time is 40min. After the ultrasonic crushing treatment is completed, the moisture content is adjusted to 78wt% to obtain a pretreated slurry.

[0040] Among them, the weight ratio of wheat straw, corn leaves, bamboo leaves, mangosteen shells and deionized water is 10:7:4:4:1500.

[0041] 2. Functional filler modification Silane coupling agent KH-550 and silane coupling agent KH-602 are added to anhydrous ethanol, stirred for 20 minutes, and then deionized water is added, and the pH is adjusted to 4.5 with hydrochloric acid, and stirred at room temperature for 10 hours to obtain a hydrolyzate; then medical stone and activated carbon are added to the hydrolyzate, and after ultrasonic dispersion, the temperature is raised to 70°C, and the reaction is stirred and kept warm for 5 hours, and then the solid is obtained by centrifugation at 7000 rpm. After washing the solid with deionized water until it is neutral, it is placed in a vacuum environment of 0.06 MPa, and dried at 85°C to obtain a functional modified filler (i.e., a hyperbranched polysiloxane composite modified filler).

[0042] Wherein, the weight ratio of silane coupling agent KH-550, silane coupling agent KH-602, anhydrous ethanol and deionized water is 4:2.1:60:2.

[0043] The weight ratio of medical stone, activated carbon and hydrolyzate is 1.6:3.3:43.

[0044] 3. Low temperature treatment After the pretreated slurry and the functional modified filler are evenly mixed, the temperature is cooled to -42°C at a cooling rate of 5°C / min, kept at this temperature for 5 hours, and then naturally warmed to room temperature. After being kept at room temperature for 10 hours, the slurry is stirred at room temperature for 1 hour to obtain a composite slurry.

[0045] The weight ratio of the pretreated slurry to the functional modified filler is 100:7.

[0046] 4. Paper processing After the composite pulp, modified nanocellulose and cationic polyacrylamide are evenly mixed, a pulping treatment is carried out, and the pulping speed is controlled to be 18000rpm and the beating degree is 45°SR to obtain a pulped material; the pulped material is subjected to a papermaking treatment, and after the paper is formed, it is dried until the moisture content of the finished paper is reduced by 28% compared with the initial moisture content, to obtain semi-dry paper.

[0047] Among them, the weight ratio of the composite pulp, modified nanocellulose and cationic polyacrylamide is 100:4:1.2.

[0048] The preparation method of modified nanocellulose is as follows: the nanocellulose is put into 10 times the weight of anhydrous ethanol, ultrasonically dispersed for 20 minutes, stirred and heated to 65°C in a nitrogen atmosphere, and the modified treatment liquid is dripped in while being kept warm; the dripping time of the modified treatment liquid is controlled to be 2 hours; after the addition of the modified treatment liquid is completed, the stirring is continued for 2 hours, and the solid is obtained by centrifugation at 12000rpm, and the solid is washed with anhydrous ethanol and dried to obtain the modified nanocellulose.

[0049] The modification treatment liquid is an anhydrous ethanol solution of dendritic polyamide-amine G2 (PAMAM G2); the concentration of the dendritic polyamide-amine G2 in the modification treatment liquid is 10.5wt%.

[0050] The weight ratio of nanocellulose to the dendritic polyamide-amine G2 in the modified treatment solution was 5:1.

[0051] 5. Coating treatment Chitosan was added into an acetic acid aqueous solution with a mass concentration of 3%, stirred and dissolved to prepare a coating solution; semi-dried paper was used as the coating substrate, and the coating solution was coated on the surface of the semi-dried paper by Mayer rod coating, and the coating amount of chitosan in the coating solution on the surface of the semi-dried paper was controlled to be 3.2 g / m 2 After coating, the coating was placed in an environment with a temperature of 85°C and dried for 20 minutes, and then transferred to an environment with a temperature of 22°C and a relative humidity of 48%RH and allowed to stand for 22 hours to obtain a natural degradable packaging material.

[0052] Wherein, the chitosan concentration in the coating solution is 1wt%.

[0053] This embodiment also provides a natural degradable packaging material prepared by the above method.

[0054] Example 2 This embodiment provides a method for preparing a natural degradable packaging material, which comprises the following steps: 1. Raw material pretreatment The wheat straw, corn leaf, bamboo leaf and mangosteen shell are washed respectively, and the surface mud and other debris are removed and then dried; then the washed and dried wheat straw, corn leaf, bamboo leaf and mangosteen shell are put into deionized water, the temperature is raised to 39°C, lipase and pectinase are added during heat preservation, and the enzyme activity of lipase in the pretreated mixture is controlled to be 23U / mL, and the enzyme activity of pectinase is controlled to be 31U / mL; after heat preservation and enzymolysis for 3 hours, the enzyme is inactivated, and then ultrasonic crushing treatment is carried out, the ultrasonic crushing treatment frequency is controlled to be 35KHz, the ultrasonic crushing treatment power is 750W, and the ultrasonic crushing treatment time is 45min. After the ultrasonic crushing treatment is completed, the moisture content is adjusted to 79wt% to obtain a pretreated slurry.

[0055] Among them, the weight ratio of wheat straw, corn leaves, bamboo leaves, mangosteen shells and deionized water is 11:7.7:4.5:4.5:1550.

[0056] 2. Functional filler modification Silane coupling agent KH-550 and silane coupling agent KH-602 were added to anhydrous ethanol, stirred for 30 minutes, and then deionized water was added, and the pH was adjusted to 4.5 with hydrochloric acid, and stirred at room temperature for 11 hours to obtain a hydrolyzate; then medical stone and activated carbon were added to the hydrolyzate, and after ultrasonic dispersion, the temperature was raised to 72°C, and the reaction was stirred and kept warm for 5.5 hours, and then the solid was obtained by centrifugation at 7500 rpm. After the solid was washed with deionized water until neutral, it was placed in a vacuum environment of 0.07 MPa, and dried at 82°C to obtain a functional modified filler (i.e., a hyperbranched polysiloxane composite modified filler).

[0057] Wherein, the weight ratio of silane coupling agent KH-550, silane coupling agent KH-602, anhydrous ethanol and deionized water is 4.07:2.15:63:2.1.

[0058] The weight ratio of medical stone, activated carbon and hydrolyzate is 1.65:3.4:44.

[0059] 3. Low temperature treatment After the pretreated slurry and the functional modified filler are evenly mixed, the temperature is cooled to -41°C at a cooling rate of 5.5°C / min, kept at this temperature for 5.5 hours, and then naturally warmed to room temperature. After standing at room temperature for 11 hours, the slurry is stirred at room temperature for 1.5 hours to obtain a composite slurry.

[0060] Among them, the weight ratio of the pretreated slurry and the functional modified filler is 100:7.2.

[0061] 4. Paper processing The composite pulp, modified nanocellulose and cationic polyacrylamide are mixed evenly, and then pulping is carried out, and the pulping speed is controlled to be 19000rpm and the beating degree is 46°SR to obtain a pulped material; the pulped material is subjected to papermaking treatment, and after the paper is formed, it is dried until the moisture content of the finished paper is reduced by 29% compared with the initial moisture content, to obtain semi-dry paper.

[0062] Among them, the weight ratio of the composite pulp, modified nanocellulose and cationic polyacrylamide is 100:4.3:1.25.

[0063] The preparation method of modified nanocellulose is as follows: the nanocellulose is put into 11 times the weight of anhydrous ethanol, ultrasonically dispersed for 30 minutes, stirred and heated to 67°C in a nitrogen atmosphere, and the modified treatment liquid is dripped in while keeping warm; the dripping time of the modified treatment liquid is controlled to be 2.3 hours; after the addition of the modified treatment liquid is completed, the stirring is continued to be kept warm for 2.2 hours, and the solid is obtained by centrifugation at 13000rpm, and the solid is washed with anhydrous ethanol and dried to obtain the modified nanocellulose.

[0064] The modification treatment liquid is an anhydrous ethanol solution of dendritic polyamide-amine G2 (PAMAM G2); the concentration of the dendritic polyamide-amine G2 in the modification treatment liquid is 11.2wt%.

[0065] The weight ratio of nanocellulose to dendritic polyamide-amine G2 in the modified treatment solution was 5.3:1.

[0066] 5. Coating treatment Chitosan was added into an acetic acid aqueous solution with a mass concentration of 3.5%, and stirred to dissolve to prepare a coating solution; semi-dried paper was used as the coating substrate, and the coating solution was coated on the surface of the semi-dried paper by Mayer rod coating, and the coating amount of chitosan in the coating solution on the surface of the semi-dried paper was controlled to be 3.2 g / m 2 After coating, the coating was placed in an environment with a temperature of 88°C and dried for 20 minutes, and then transferred to an environment with a temperature of 23°C and a relative humidity of 50%RH and allowed to stand for 23 hours to obtain a natural degradable packaging material.

[0067] The chitosan concentration in the coating solution is 1.1 wt %.

[0068] This embodiment also provides a natural degradable packaging material prepared by the above method.

[0069] Example 3 This embodiment provides a method for preparing a natural degradable packaging material, which comprises the following steps: 1. Raw material pretreatment The wheat straw, corn leaves, bamboo leaves and mangosteen shells are washed respectively, and the surface mud and other debris are removed and then dried; then the washed and dried wheat straw, corn leaves, bamboo leaves and mangosteen shells are put into deionized water, the temperature is raised to 40°C, lipase and pectinase are added while being kept warm, and the enzyme activity of lipase in the pretreated mixture is controlled to be 24U / mL, and the enzyme activity of pectinase is controlled to be 32U / mL; after keeping warm for 3.5 hours of enzymolysis, the enzyme is killed, and then ultrasonic crushing treatment is carried out, the ultrasonic crushing treatment frequency is controlled to be 36KHz, the ultrasonic crushing treatment power is 800W, the ultrasonic crushing treatment time is 50min, and after the ultrasonic crushing treatment is completed, the moisture content is adjusted to 80wt% to obtain a pretreated slurry.

[0070] Among them, the weight ratio of wheat straw, corn leaves, bamboo leaves, mangosteen shells and deionized water is 12:8:5:5:1600.

[0071] 2. Functional filler modification Silane coupling agent KH-550 and silane coupling agent KH-602 were added to anhydrous ethanol, stirred for 40 minutes, and then deionized water was added, and the pH was adjusted to 5 with hydrochloric acid, and stirred at room temperature for 12 hours to obtain a hydrolyzate; then medical stone and activated carbon were added to the hydrolyzate, and after ultrasonic dispersion, the temperature was raised to 75°C, and the mixture was stirred and reacted for 6 hours, and then centrifuged at 8000 rpm to obtain a solid. The solid was washed with deionized water until neutral, placed in a vacuum environment of 0.08 MPa, and dried at 80°C to obtain a functional modified filler (i.e., a hyperbranched polysiloxane composite modified filler).

[0072] Wherein, the weight ratio of silane coupling agent KH-550, silane coupling agent KH-602, anhydrous ethanol and deionized water is 4.1:2.2:65:2.2.

[0073] The weight ratio of medical stone, activated carbon and hydrolyzate is 1.7:3.5:45.

[0074] 3. Low temperature treatment After the pretreated slurry and the functional modified filler are evenly mixed, the temperature is cooled to -40°C at a cooling rate of 6°C / min, kept at this temperature for 6 hours, and then naturally warmed to room temperature. After standing at room temperature for 12 hours, the slurry is stirred at room temperature for 2 hours to obtain a composite slurry.

[0075] Among them, the weight ratio of the pretreated slurry and the functional modified filler is 100:7.3.

[0076] 4. Paper processing After the composite pulp, modified nanocellulose and cationic polyacrylamide are evenly mixed, a pulping treatment is carried out, and the pulping speed is controlled to be 20000rpm and the beating degree is 48°SR to obtain a pulped material; the pulped material is subjected to a papermaking treatment, and after the paper is formed, it is dried until the moisture content of the finished paper is reduced by 30% compared with the initial moisture content, to obtain semi-dry paper.

[0077] Among them, the weight ratio of composite pulp, modified nanocellulose and cationic polyacrylamide is 100:4.5:1.3.

[0078] The preparation method of modified nanocellulose is as follows: the nanocellulose is put into 12 times the weight of anhydrous ethanol, ultrasonically dispersed for 40 minutes, stirred and heated to 68°C in a nitrogen atmosphere, and the modified treatment liquid is dripped in while keeping warm; the dripping time of the modified treatment liquid is controlled to be 2.5 hours; after the addition of the modified treatment liquid is completed, the stirring is continued for 2.5 hours, and solid matter is obtained by centrifugation at 13000 rpm, and the solid matter is washed with anhydrous ethanol and dried to obtain modified nanocellulose.

[0079] The modification treatment liquid is an anhydrous ethanol solution of dendritic polyamide-amine G2 (PAMAM G2); the concentration of the dendritic polyamide-amine G2 in the modification treatment liquid is 12wt%.

[0080] The weight ratio of nanocellulose to dendritic polyamide-amine G2 in the modified treatment solution was 5.5:1.

[0081] 5. Coating treatment Chitosan was added into an acetic acid aqueous solution with a mass concentration of 4%, and stirred to dissolve to prepare a coating solution; semi-dried paper was used as the coating substrate, and the coating solution was coated on the surface of the semi-dried paper by Mayer rod coating, and the coating amount of chitosan in the coating solution on the surface of the semi-dried paper was controlled to be 3.2 g / m 2 After coating, the coating was placed in a 90°C environment for drying for 20 minutes, and then transferred to a 24°C, 52%RH environment for static equilibrium for 24 hours to obtain a natural degradable packaging material.

[0082] Wherein, the concentration of chitosan in the coating solution is 1.2wt%.

[0083] This embodiment also provides a natural degradable packaging material prepared by the above method.

[0084] Comparative Example 1 The technical solution of Example 2 is adopted, but the differences are: 1) bamboo leaves and mangosteen shells are omitted in the raw material pretreatment; 2) the functional filler modification step is omitted, and medical stone and activated carbon are directly substituted for the functional modified filler and mixed with the pretreated slurry; and the weight ratio of medical stone to activated carbon is 1.65:3.4.

[0085] Comparative Example 2 The technical solution of Example 2 is adopted, but the differences are: 1) the low temperature treatment step is omitted, and the pretreated pulp and the functional modified filler are directly mixed evenly to obtain a composite pulp; 2) in the paper-forming process, unmodified nanocellulose is used instead of modified nanocellulose.

[0086] The air permeability, oil resistance, oxygen barrier performance, water vapor permeability, tensile strength, tear strength and burst resistance of the packaging materials of Examples 1-3 and Comparative Examples 1-2 were tested respectively.

[0087] The specific test method of air permeability refers to TAPPI standard (T460 om-06), and the air permeability of each packaging material is measured by using Gurley air permeability meter.

[0088] The specific testing method for oil resistance refers to the TAPPI standard (T559 pm-96), which measures the oil resistance level of each packaging material and the surface tension between each packaging material and castor oil; among them, the highest oil resistance level is 12 and the lowest is 0.

[0089] The oxygen barrier performance is measured by using a Y110 oxygen permeation analyzer (pressure difference method) in an environment of temperature 23±0.1℃ and relative humidity 50±1%RH to detect the oxygen permeation rate per unit area of ​​each packaging material per unit time.

[0090] The specific test method for water vapor permeability refers to the standard ASTM E96 "Standard Test Method for Water Vapor Permeability of Materials", which tests the mass of water vapor passing through a unit area per unit time for each packaging material.

[0091] The specific test method for tensile strength refers to TAPPI standard (T494 om-13).

[0092] The specific test method for tear strength refers to TAPPI standard (T414 om-12).

[0093] For the specific test method of burst resistance, please refer to TAPPI standard (T403 om-15).

[0094] The specific test results are shown in the following table:

[0095] Further, referring to the relevant methods of the standard GB / T 21866-2008 "Determination of antibacterial properties of antibacterial paper and paperboard", the antibacterial rates of Escherichia coli and golden yellow common cocci of the packaging materials of Examples 1-3 and Comparative Examples 1-2 were tested respectively. Specifically, the antibacterial rates of each packaging material were tested when the constant temperature was cultured for 48h and 240h at a temperature of 37°C. The specific test results are shown in the following table:

[0096] Furthermore, the packaging materials of Example 2 and Comparative Examples 1-2 were placed in an environment with a temperature of 55°C and a relative humidity of 90%RH, and were taken out after standing for 7 days. After standing at room temperature for 24 hours, the air permeability, oil resistance level, oxygen barrier performance, tensile strength, 48h antibacterial rate of Escherichia coli, and 48h antibacterial rate of Staphylococcus aureus of each packaging material were measured by the above method. The specific test results are shown in the following table:

[0097] It can be seen that the preparation method of the natural degradable packaging material of the present invention selects wheat straw, corn leaves, bamboo leaves, and mangosteen shells as fiber raw materials in the raw material pretreatment step, and after enzymolysis by lipase and pectinase, ultrasonic crushing is performed to obtain a pretreated slurry; through the long fiber characteristics of bamboo leaves and the antibacterial and antioxidant properties of mangosteen shells, combined with composite enzymolysis and ultrasonic crushing processes, it is possible to give the packaging material antibacterial properties, inhibit the growth of microorganisms, improve the mechanical properties and barrier properties of the packaging material, and provide the structural stability of the fiber base paper; in the functional filler modification step, the silane coupling agent KH -550, silane coupling agent KH-602 are subjected to composite hydrolysis, and then contacted with medical stone and activated carbon, and in-situ condensation is carried out on the surface to generate hyperbranched polysiloxane, thereby obtaining a hyperbranched polysiloxane composite modified filler (functional modified filler); while improving the uniformity of the distribution of medical stone and activated carbon in the pretreated pulp, the hyperbranched polysiloxane of the functional modified filler forms a strong interface bond with the fiber in the pretreated pulp, thereby improving the fiber structure stability of the fiber base paper and improving the mechanical properties of the packaging material (such as tensile strength, bursting resistance, etc.); and the functional modified filler has a filling effect on the fiber gaps, Improve the barrier and oil-proof properties of packaging materials, and improve the overall stability of packaging materials; in the low-temperature treatment step, the pretreated pulp is mixed with the functional modified filler and then subjected to low-temperature treatment, and ice crystals are formed by the water in the pulp at low temperature, which further improves the interface bonding between the pretreated pulp and the functional modified filler, improves the uniformity of raw material mixing, and optimizes the overall performance of packaging materials; in the paper-forming step, the composite pulp, modified nanocellulose, and cationic polyacrylamide are mixed for pulping, papermaking, and drying, and the nanocellulose modified by the dendritic polyamide-amine G2 has a bonding and filling effect on the fibers. Use, further improve the mechanical properties, barrier properties and oil resistance of packaging materials, optimize the overall stability of packaging materials; in the coating process, chitosan solution is used as the coating liquid to coat the semi-dry paper, so as to further improve the barrier properties, oil resistance and antibacterial properties of packaging materials; the aforementioned technical means cooperate and work synergistically with each other, which can effectively avoid the problem of poor combination performance between packaging materials and functional auxiliary ingredients, effectively improve the mechanical properties, oxygen barrier properties, moisture barrier properties and oil resistance of packaging materials; and further improve the stability of packaging materials in high temperature and high humidity environments, so as to maintain good performance for a long time.

[0098] It can be seen from Comparative Example 1 that after omitting bamboo leaves and mangosteen shells in the raw material pretreatment and omitting the functional filler modification step, it is impossible to use the long fiber characteristics of bamboo leaves and the antibacterial and antioxidant characteristics of mangosteen shells to cooperate with other pulp raw materials, and it is also impossible to improve the uniformity of filler distribution and its interface bonding with the fiber. The added filler components affect the fiber structure of the fiber base paper, and the analytical performance, barrier performance, oil resistance and overall stability of the packaging material are deteriorated to a certain extent. Specifically, the air permeability, oil resistance and barrier performance of the packaging material are deteriorated, the mechanical properties are reduced; and the air permeability, oil resistance level, oxygen permeability, tensile strength, etc. are reduced after standing in a high temperature and high humidity environment.

[0099] Comparative Example 2 shows that after omitting the low-temperature treatment step and the modified nanocellulose in the paper-forming process, the interface bonding between the pre-treated pulp and the functional modified filler cannot be further improved, and the mechanical properties, barrier properties, oil resistance and overall stability of the packaging material cannot be further improved through the bonding and filling effect of the nanocellulose modified by the dendritic polyamide-amine G2 on the fibers. Specifically, the air permeability, oil resistance and barrier properties of the packaging material deteriorate, and the mechanical properties are significantly reduced; the stability in high temperature and high humidity environment is poor, and the performance cannot be maintained for a long time.

[0100] Unless otherwise specified, all percentages used in the present invention are by mass.

[0101] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a natural degradable packaging material, characterized in that: The method consists of the following steps: raw material pretreatment, functional filler modification, low temperature treatment, paper forming treatment, and coating treatment; The method for pretreating the raw materials is as follows: putting wheat straw, corn leaves, bamboo leaves and mangosteen shells into deionized water, enzymolyzing with lipase and pectinase, and then subjecting to ultrasonic crushing treatment to adjust the water content to 78-80wt% to prepare a pretreated slurry; The method for modifying the functional filler is as follows: hydrolyzing silane coupling agent KH-550 and silane coupling agent KH-602 to obtain a hydrolyzate; adding medical stone and activated carbon into the hydrolyzate, keeping the temperature at 70-75° C. for reaction, and separating to obtain a solid; washing and drying the solid to obtain a functional modified filler; The low-temperature treatment method is to mix the pretreated slurry and the functional modified filler uniformly, cool the mixture to -42°C to -40°C, keep the mixture warm and then return the mixture to room temperature to obtain a composite slurry. The paper processing method comprises the following steps: mixing the composite pulp, modified nanocellulose and cationic polyacrylamide uniformly, and then beating the pulp to obtain a pulped material; making a paper of the pulped material, and drying the paper after forming the paper to obtain semi-dry paper; The preparation method of the modified nanocellulose is to treat the nanocellulose with a modification treatment liquid; the modification treatment liquid is an anhydrous ethanol solution of dendritic polyamide-amine G2; The coating treatment method is to use chitosan solution as coating liquid, coat it on the surface of semi-dried paper, dry it, and place it for equilibrium to obtain a natural degradable packaging material.

2. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the raw material pretreatment, the lipase activity is controlled to be 22-24 U / mL, the pectinase activity is controlled to be 30-32 U / mL; the enzymolysis temperature is 38-40°C, and the enzymolysis time is 2.5-3.5 h; The ultrasonic crushing treatment frequency is 32-36KHz, the ultrasonic crushing treatment power is 700-800W, and the ultrasonic crushing treatment time is 40-50min.

3. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the raw material pretreatment, the weight ratio of wheat straw, corn leaves, bamboo leaves, mangosteen shells and deionized water is 10-12:7-8:4-5:4-5:1500-1600.

4. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the functional filler modification, silane coupling agent KH-550 and silane coupling agent KH-602 are added to anhydrous ethanol, and after being evenly dispersed, deionized water is added, the pH is adjusted to 4.5-5, and stirred at room temperature for 10-12 hours to obtain a hydrolyzate; The weight ratio of silane coupling agent KH-550, silane coupling agent KH-602, anhydrous ethanol and deionized water is 4-4.1:2.1-2.2:60-65:2-2.

2.

5. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the modification of the functional filler, the reaction time at 70-75°C is 5-6h; The weight ratio of medical stone, activated carbon and hydrolyzate is 1.6-1.7:3.3-3.5:43-45.

6. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the low temperature treatment, the cooling rate is 5-6°C / min; the heat preservation and standing time is 5-6h; The weight ratio of the pretreated slurry to the functional modified filler is 100:7-7.

3.

7. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the paper forming process, the beating speed is controlled to be 18000-20000 rpm, and the beating degree is 45-48° SR; After papermaking and forming, the moisture content of the dried paper is reduced by 28-30% compared with the initial moisture content; The weight ratio of the composite pulp, the modified nanocellulose and the cationic polyacrylamide is 100:4-4.5:1.2-1.

3.

8. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: The method for modifying nanocellulose is as follows: adding nanocellulose into anhydrous ethanol, dispersing the nanocellulose evenly, heating the nanocellulose to 65-68° C. under the protection of an inert gas, and dripping a modified treatment solution while maintaining the temperature; After the modified treatment liquid is added dropwise, the mixture is stirred at a temperature of 2-2.5 hours, and a solid is separated and washed and dried to obtain modified nanocellulose. The concentration of the dendritic polyamide-amine G2 in the modified treatment solution is 10.5-12wt%; The weight ratio of the nanocellulose to the dendritic polyamide-amine G2 in the modified treatment solution is 5-5.5:

1.

9. The method for preparing the natural degradable packaging material according to claim 1, characterized in that: In the coating process, the coating amount of chitosan in the coating liquid on the semi-dried paper surface is controlled to be 3.2-3.5 g / m 2 ; The drying temperature is 85-90℃ and the drying time is 15-20min; The temperature of static equilibrium is 22-24°C, the relative humidity of static equilibrium is 48-52%RH, and the time of static equilibrium is 22-24h; The concentration of chitosan in the coating solution is 1-1.2wt%.

10. A natural degradable packaging material, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Application of cationic dendritic macromolecular papermaking retention and drainage aid agent

    CN101892610A

  • Method for improving slurry-made paper strength, and slurry and paper prepared by the method

    CN104047206A

  • Food packaging paper

    CN107366193A

  • Preparation method of modified aluminosilicate composite rubber sealing papermaking plate

    CN110644287A

  • High-antibacterial degradable preservative film and processing technology thereof

    CN116622203A